Bologna centrale Station: a spatial and sound analysis - Buda, Irene; Ferravante, Maria Rosa; Marinacci, Giulia; Menga, Valeria (E|C, 2020)
The following article is an analysis of the soundscape of a crucial place for the everyday life in an important city located in the north of Italy: the Central Railway Station in Bologna. Specifically, we have taken into consideration three main areas: Medaglie d’Oro Square, the main Hall and the hallway next to the first railroad track. The analysis connects some of the exclusively architectonic elements of the place – which are a background for the other elements – to those temporary, both animate and inanimate. Indeed, the sound is inherently linked to practices, uses and meanings actualized by the users. At the same time, it sets the rhythms, it verifies or denies architectonic thresholds and limits, and it presents the same isotopies. Moreover, we talk about the itineraries allowed by thresholds and limits, and agentive configurations on the narrative plane. In conclusion, through this research we are able to observe an occasional lack of correspondence between architectonic and auditory elements that nevertheless translates to cohesion between the three main areas taken into consideration. We used direct listening and observation of the situations described, as well as audio recordings during different moments of the day (morning, afternoon and evening) and different days of the week (both weekdays and weekends).